A rare case of spontaneous nephrocutaneous fistula - Bansod, Atish N.; Mirajkar, Girish N.; Umalkar, Rohan; Mishra, Sarvagya; Kumar, Ankur; Nadar, Premalatha (International Surgery Journal, 2020)
Acute and chronic pyelonephritis are known afflictions to the kidney in diabetics and in patients of abnormal urinary anatomy. And its presentation as a spontaneous sinus opening on the anterior abdominal wall is a rare phenomenon. We present one such rare case of a 71-year-old male with pus discharge from the anterior abdominal wall for 7 months. On investigating, it was found to be a nephrocutaneous fistula arising from the left non-functional kidney. This was dealt with left nephrectomy along with excision of the sinus tract. Though a very rare condition, a possibility of nephrocutaneous fistula must be kept when dealing with discharging sinus in lumbar region.